Aplikasi Penerimaan Peserta Santri Baru Berbasis Web Pada Yayasan Ulul’Ilmi Qoimam Bil Qisthi - Chandra Sidiq Prayoga; Muhamad Taufik; Raditya Bagaskara; Wasis Haryono (CV. Multi Kreasi Media, 2023)
The Yayasan Ulul'Ilmi Qoimam Bil Qisthi is an educational institution, in the field of new student admissions, the Yayasan Ulul'Ilmi Qoimam Bil Qisthi still uses the manual method, therefore we are trying to build a design for example. Research by the Yayasan Ulul'Ilmi Bil Qisthi to create a web-based data collection system namely. A new web-based Santri Participation Approval application to make it easier for users to find conclusions about registration information. The purpose of this research is to apply information technology in education, especially the Yayasan Ulul'Ilmi Qoimam Bil Qisthi, and to create a fast and accurate education system that makes it easy to collect information for students, so that online education is created. new student application planning system. In addition, interactive screens make it easy for users to gather information about students. As for the PHP programming language, MySQL is a language and database that work together. The waterfall method was used in the development of this system, so that it can be interpreted that this system is feasible to implement if the new student admission application is implemented at the Yayasan Ulul'Ilmi Qoimam Bil Qisthi.